Long-term exposure to road traffic noise, ambient air pollution, and cardiovascular risk factors in the HUNT and lifelines cohorts. (31st May 2017) - Cai, Yutong; Hansell, Anna L.; Blangiardo, Marta; Burton, Paul R.; ,; de Hoogh, Kees; Doiron, Dany; Fortier, Isabel; Gulliver, John; Hveem, Kristian; Mbatchou, Stéphane; Morley, David W.; et al.
Abstract: Aims: Blood biochemistry may provide information on associations between road traffic noise, air pollution, and cardiovascular disease risk. We evaluated this in two large European cohorts (HUNT3, Lifelines). Methods and results: Road traffic noise exposure was modelled for 2009 using a simplified version of the Common Noise Assessment Methods in Europe (CNOSSOS-EU). Annual ambient air pollution (PM10, NO2 ) at residence was estimated for 2007 using a Land Use Regression model. The statistical platform DataSHIELD was used to pool data from 144 082 participants aged ≥20 years to enable individual-level analysis. Generalized linear models were fitted to assess cross-sectional associations between pollutants and high-sensitivity C-reactive protein (hsCRP), blood lipids and for (Lifelines only) fasting blood glucose, for samples taken during recruitment in 2006–2013. Pooling both cohorts, an inter-quartile range (IQR) higher day-time noise (5.1 dB(A)) was associated with 1.1% [95% confidence interval (95% CI: 0.02–2.2%)] higher hsCRP, 0.7% (95% CI: 0.3–1.1%) higher triglycerides, and 0.5% (95% CI: 0.3–0.7%) higher high-density lipoprotein (HDL); only the association with HDL was robust to adjustment for air pollution. An IQR higher PM10 (2.0 µg/m 3 ) or NO2 (7.4 µg/m 3 ) was associated with higher triglycerides (1.9%, 95% CI: 1.5–2.4% and 2.2%, 95% CI: 1.6–2.7%), independent of adjustment for noise. Additionally for NO2, a significant association with hsCRP (1.9%, 95% CI: 0.5–3.3%) was seen. In Lifelines, an IQR higher noise (4.2 dB(A)) and PM10 (2.4 µg/m 3 ) was associated with 0.2% (95% CI: 0.1–0.3%) and 0.6% (95% CI: 0.4–0.7%) higher fasting glucose respectively, with both remaining robust to adjustment for air/noise pollution. Conclusion: Long-term exposures to road traffic noise and ambient air pollution were associated with blood biochemistry, providing a possible link between road traffic noise/air pollution and cardio-metabolic disease risk.